Revalidating the Taiwanese Self-Regulation Questionnaire (New TSSRQ) and Exploring Its Relationship With College Students’ Psychological Well-Being - Chen, Yang-Hsueh; Lin, Yu-Ju (Frontiers in Psychology, 2020)
Self-regulation (SR) is a vital trait whereby people adapt to the environments and achieve goals, yet measurements of general SR remain scant in Asian countries. Due to insufficient items in several dimensions, in this study we revised and revalidated our previous work of the Short Self-Regulation Questionnaire for Taiwanese college students (TSSRQ) by incorporating student perspectives and aspects of affective/motivation regulation. Through exploratory and confirmatory factor analyses, we validated the “New TSSRQ” which contained 39 items in 7 factors, including Proactiveness (PA), Self-management (SM), Goal Setting (GS), Mindfulness (MF), Goal Attainment (GA), Adjustment (AD), and Motivation (MO). Subsequently, we explored the correlation between New TSSRQ dimensions and those of the Scale of Psychological Well-being (SPWB) as a source of validity evidence. Findings indicated that SR and PWB are highly correlated, especially for Mindfulness and Proactiveness dimensions. Implications of this study were discussed along with practical suggestions to leverage college students’ mindfulness, proactiveness, and self-regulation in general.